THEORETICAL ISSUES ON THE USE OF ISOPHIC COMPOUNDS IN THE WORK "ANSOB US-SALOTIN AND TAWARIKH UL-HAVAQIN" (Scientific journal of the Fergana State University, 2024)
In this article, the theoretical issues related to the use of isophical compounds in Mizoolim Mushrif's work "Ansab us-salatin wa tawarikh ul-hawaqin" are thoroughly analyzed. The Persian-Tajik language served as a common literary language of many peoples even in the middle of the 19th century. Along with the original Turkish words, Persian-Tajik and Arabic lexical layers also have a certain weight in the language lexicon of Mirzoolim Mushrif's "History of the Kokhan Khanate". For that period, this phenomenon was considered a literary norm. Scholars have stated in their research that the scholars and writers who created in the Middle Ages used Persian and Tajik words in their historical works. At the same time, it is thought about the expression of isophical compounds within the framework of different word groups, the connection and expression of demonstrative and object, determiner and determined.